Unusual Market Activity Impact on Abnormal Liquidity Risk, Abnormal Volatility, and Abnormal Return in Indonesia Capital Market - Kurnia Putri, Famy; Christina Pasaribu, Maria; Hanggraeni, Dewi (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the influence of the management control system consisting of enabling control and constraining control on organizational performance and management innovation in heavy equipment and truck companies operating in North Kalimantan. Management control systems that involve enabling controls that encourage organizational creativity and development, as well as constraining controls that provide constraints to ensure efficient operations, are analyzed to see their impact on management innovation and organizational performance. This study uses a quantitative descriptive approach by collecting primary data through a survey of 57 supervisors in 10 relevant companies. The data was analyzed using the Structural Equation Modeling (SEM) method with PLS 4 software. The results of the study show that enabling control has a significant positive influence on organizational performance, while constraining control, both through a limitation system and diagnostic control, has a negative effect on organizational performance, although the diagnostic control system plays a positive role in encouraging management innovation. These findings indicate that to improve organizational performance, companies need to make more intensive use of enabling controls, while considering the implementation of diagnostic control systems that can support innovation